COMPARATIVE ANALYSIS OF TECHNOLOGIES FOR HYDROGEN PRODUCTION FROM PLASTIC WASTE (International Congress on Economics, Management and Business Studies, 2026)
This article presents a comparative scientific analysis of the main technologies used for hydrogen production from plastic waste, with emphasis on thermochemical, catalytic, microwave-assisted, plasma-assisted, hydrothermal, and emerging electrochemical or photo-reforming routes. The relevance of the topic is determined by two parallel global challenges: the rapid accumulation of plastic waste and the need to expand low-carbon hydrogen production. According to the OECD, global plastics production increased from 234 million tonnes in 2000 to 460 million tonnes in 2019, while plastic waste rose from 156 million tonnes to 353 million tonnes over the same period; only about 9% of plastic waste was ultimately recycled, whereas 19% was incinerated and almost half was landfilled. At the same time, conventional hydrogen production remains strongly fossil-dependent: the International Energy Agency reported that global hydrogen production emitted 920 Mt CO₂ in 2023, with nearly two-thirds produced from unabated natural gas and about one-fifth from unabated coal. In this context, plastic-to-hydrogen conversion can be considered not as a universal solution to plastic pollution, but as a technically significant waste-to-value pathway for non-recyclable, mixed, contaminated, or multilayer plastic streams. The article compares conventional pyrolysis, pyrolysis–catalytic steam reforming, gasification, microwave-assisted pyrolysis, plasma-assisted conversion, supercritical water treatment, catalytic dry reforming, oxidative steam reforming, and emerging routes such as photo-reforming and electro-reforming. The comparison shows that pyrolysis alone is technically simple but produces hydrogen-rich gases only as one fraction of a wider oil–gas–char product spectrum, while integrated pyrolysis–steam reforming–water gas shift systems provide higher hydrogen selectivity and better compatibility with pressure swing adsorption or membrane separation. Gasification is more suitable for continuous large-scale operation and mixed feedstocks but requires strict control of temperature, steam/carbon ratio, equivalence ratio, tar formation, chlorine release, and downstream gas cleaning. Microwave-assisted pyrolysis offers selective heating, lower tar formation potential, and energy-saving prospects, but scale-up is limited by microwave penetration depth, feedstock dielectric variability, and equipment cost. Plasma and supercritical water processes can process difficult waste streams but face high energy intensity, reactor material challenges, and economic uncertainty. The study concludes that the most industrially realistic pathway in the near term is not a single technology, but a hybrid system combining feedstock pretreatment, dechlorination, staged pyrolysis or gasification, catalytic reforming, water–gas shift, hydrogen purification, and carbon management.
Keywords: plastic waste, hydrogen production, pyrolysis, gasification, steam reforming, catalytic reforming, microwave-assisted pyrolysis, plasma gasification, syngas, circular economy, low-carbon hydrogen, waste-to-energy.